Programa de escuela de padres y compromiso parental percibido por los estudiantes de primaria de la institución educativa N° 6010368 comunidad San Juan de Barranco, Caballococha 2024 - Witancort Barboza, Efrain (2025)
The main purpose of this research was to determine the effects of the School for Parents Program on the development of parental commitment perceived by the students of the Educational Institution No. 6010368. This is a quantitative research whose design is quasi-experimental in its two levels with pre-test and post-test with only one group. The population consisted of 39 students and 68 parents. The sample used was 100% of the total population. The direct observation and survey techniques were applied and the instruments used were a checklist and a questionnaire of questions. The most relevant conclusions were the following: In the post-test evaluation, the results were: in school-based commitment the expected high level reached 44%; the home-based commitment dimension managed to reach an expected level of 44%; and the dimension commitment based on school meetings was found with 41% of the expected level. The results show a high and significant positive correlation (Rho=0.770; p=0.000), suggesting that the implementation of the “Parenting School” Program has a positive and significant impact on the parental commitment perceived by the students, supporting the hypothesis of the study.